The role of three dimensional transesophageal echocardiography novel-score in the success of redo percutaneous balloon mitral valvuloplasty - Memiç Sancar, Kadriye; Güler, Gamze Babur; Tanboğa, Halil İbrahim; Demir, Ali Rıza; Şahin, Ahmet Anıl; Taşbulak, Ömer; Tükenmez Karakurt, Seda; Aktemur, Tuğba; Avcı, Yalçın; Bulut, Ümit; Tekin, Meltem; Güler, Ekrem; et al. (Springer, 2022)
Mitral valve commissure evaluation is known to be important in the success of percutaneous balloon mitral valvuloplasty (PBMV) and Wilkins score (WS) is used in clinical practice. In our study, we aimed to determine whether WS in redo PBMV is sufficient in the success of procedure and additionally we have evaluated a novel scoring system including three dimensional (3D) transesophageal echocardiography (TEE) of the mitral valve structure before redo PBMV in terms of success of the procedure. Fifty patients who underwent redo PBMV were included in the study. The patients were divided into two groups according to the success of the Redo PBMV procedure which was defined as post-procedural MVA ? 1.5 cm2 and post-procedural mitral regurgitation less than moderate by echocardiographic evaluation after PBMV. A novel score based on 3D TEE findings was created by analyzing the images recorded before Redo PBMV and by evaluating the mitral commissure and calcification. The role of traditional WS and novel score in the success of the procedure were investigated. In the study group, 36 patients (72%) had successful redo PBMV procedure. WS was 8 (IQR 7–9) and novel 3D TEE score was found 4 (IQR 3–4) in the whole study group. While no statistically significant relationship was found between WS and procedural success (p = 0.187), a statistically significant relationship was found between novel 3D TEE score and procedural success (p = 0.042). Specifically, the procedural successes rate was > 90% when novel 3D TEE score was < 4. The novel 3D TEE score might be an informative scoring system in the selection of suitable patients for successful redo PBMV, especially in patients who are considered for surgery due to the high WS.
Keywords: Balloon Mitral Valvuloplasty; Commissural Calcification; Commissural Fusion; Transesophageal Echocardiography; Wilkins Score